Theoretical Health and Medical Practice. Issue 3 (July 2015) - Krueger, James
Abstract : Theoretical accounts of health attempt to ground the concept in the relevant underlying biological facts. Discussions of such accounts have largely focused on whether they successfully identify necessary and sufficient conditions for a state to count as pathological. Correctly accounting for examples of pathology, however, is not the only basis for evaluating an understanding of disease. Here I argue that we should expect any understanding of health and disease to be consistent with the view that medicine's central aim is health promotion. I argue that the theoretical account of health offered by Christopher Boorse faces particular difficulties in this regard.